2019
DOI: 10.1093/mnras/stz2822
|View full text |Cite
|
Sign up to set email alerts
|

MusE GAs FLOw and Wind (MEGAFLOW) – III. Galactic wind properties using background quasars

Abstract: We present results from our on-going MusE GAs FLOw and Wind (MEGAFLOW) survey, which consists of 22 quasar lines-of-sight, each observed with the integral field unit (IFU) MUSE and the UVES spectrograph at the ESO Very Large Telescopes (VLT). The goals of this survey are to study the properties of the circum-galactic medium around z ∼ 1 star-forming galaxies. The absorption-line selected survey consists of 79 strong Mg ii absorbers (with rest-frame equivalent width (REW) 0.3Å) and, currently, 86 associated gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
141
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(164 citation statements)
references
References 129 publications
14
141
6
Order By: Relevance
“…Bordoloi et al (2011) found a strong azimuthal dependence of Mg II absorption, implying the presence of a bipolar outflow aligned along the disc rotation axis. Concomitantly, Bouché et al (2012) and Kacprzak, Churchill & Nielsen (2012) found a bimodal distribution of azimuthal angles hosting strong Mg II absorption, suggestive of bipolar outflows contributing to the cold gas cross-section (Schroetter et al 2019;Martin et al 2019b). Such signatures are also found in hotter gas phases including ionized gas traced by OVI absorption (Kacprzak et al 2015b).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Bordoloi et al (2011) found a strong azimuthal dependence of Mg II absorption, implying the presence of a bipolar outflow aligned along the disc rotation axis. Concomitantly, Bouché et al (2012) and Kacprzak, Churchill & Nielsen (2012) found a bimodal distribution of azimuthal angles hosting strong Mg II absorption, suggestive of bipolar outflows contributing to the cold gas cross-section (Schroetter et al 2019;Martin et al 2019b). Such signatures are also found in hotter gas phases including ionized gas traced by OVI absorption (Kacprzak et al 2015b).…”
mentioning
confidence: 81%
“…Early efforts started with the AO-equipped near-infrared spectrograph VLT/SINFONI (Bouché et al 2007b;Péroux et al 2011;Péroux et al 2013Péroux et al , 2016Schroetter et al 2015). The potential of this technique for studying the CGM with the wide-field optical spectrograph VLT/MUSE has been further demonstrated (Bouché et al 2016;Schroetter et al 2016;Schroetter et al 2019;Zabl et al 2019;Muzahid et al 2020;Lofthouse et al 2020) as well as with the high spectral resolution optical spectrograph Keck/KCWI (Martin et al 2019a;Nielsen et al 2020). At z abs <1, the MUSE-ALMA Halos survey has measured the kinematics of the neutral, molecular, and ionized gas of the multiphase CGM (Péroux et al 2017;Klitsch et al 2018;Rahmani et al 2018a, b;Péroux et al 2019;Hamanowicz et al 2020).…”
mentioning
confidence: 99%
“…Several studies of Mg II-galaxy pairs have in fact reported that the distribution of Mg II absorption is not isotropic around galaxies (e.g. Bordoloi et al 2011;Bouché et al 2012;Kacprzak et al 2012;Lan & Mo 2018;Martin et al 2019;Schroetter et al 2019;Zabl et al 2019), with Mg II absorption clustering either in the direction of the major or minor axis. These observations are often interpreted with models in which the Mg II absorbing gas traces either biconical outflows perpendicular to the galaxy disc along the minor axis or co-rotating/accreting gas along the galaxy major axis.…”
Section: Azimuthal Distribution Of Mg II Absorbersmentioning
confidence: 99%
“…The major result from these studies is that the Mg ii absorbing gas is not isotropically distributed around the galaxies (e.g. Bordoloi et al 2011;Bouché et al 2012; Kacprzak et al 2012;Lan et al 2014;Lan & Mo 2018;Zabl et al 2019;Martin et al 2019;Schroetter et al 2019). Instead, the observations support a two-component geometry: a bi-conical outflow perpendicular to the galaxy disk and an extended gas disk approximately co-planar with the stellar disk.…”
Section: Introductionmentioning
confidence: 96%
“…This allows to split the Mg ii absorber sightlines into an outflow and a disk sub-sample, which can be used to study the kinematics of the outflows (e.g. Bouché et al 2012;Kacprzak et al 2014;Muzahid et al 2015;Schroetter et al 2015Schroetter et al , 2016Schroetter et al , 2019Rahmani et al 2018b;Martin et al 2019) and the extended gas accretion disks (e.g. Steidel et al 2002;Chen et al 2005;Kacprzak et al 2010Kacprzak et al , 2011bBouché et al 2013Bouché et al , 2016Ho et al 2017;Rahmani et al 2018a;Zabl et al 2019), respectively.…”
Section: Introductionmentioning
confidence: 99%